2021
DOI: 10.35848/1882-0786/ac39b0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing time and pressure on electrical activation and surface morphology of Mg-implanted GaN annealed at 1300 °C in ultra-high-pressure nitrogen ambient

Abstract: We performed an isothermal annealing study on Mg-implanted GaN at 1300 °C in an ultra-high-pressure (1 GPa) nitrogen ambient. Annealing for more than 30 min resulted in a high acceptor activation ratio and a low compensation ratio that were comparable to those obtained with annealing at 1400 °C for 5 min. We also performed annealing at 1300 °C in a reduced nitrogen pressure of 300 MPa which makes us possible to expand the inner diameter of annealing equipment in the future. High electrical activation, similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Recently, Sakurai and co-workers reported that the ultrahigh-pressure annealing (UHPA) process is effective for activating implanted p-type dopant (Mg). [14][15][16][17][18][19][20][21][22] In this process, Mg-implanted GaN is annealed at a high temperature (up to 1480 °C) under a high N 2 pressure (1 GPa) without forming a surface protection film on the sample. They reported that the activation rate of Mg exceeded 70% with UHPA, and the carrier mobility was close to that of epitaxial p-type GaN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Sakurai and co-workers reported that the ultrahigh-pressure annealing (UHPA) process is effective for activating implanted p-type dopant (Mg). [14][15][16][17][18][19][20][21][22] In this process, Mg-implanted GaN is annealed at a high temperature (up to 1480 °C) under a high N 2 pressure (1 GPa) without forming a surface protection film on the sample. They reported that the activation rate of Mg exceeded 70% with UHPA, and the carrier mobility was close to that of epitaxial p-type GaN.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Although these works have shown that UHPA is a promising postimplantation process, the formation of secondary defects, such as dislocations, precipitates, and stacking faults, was observed after annealing. [21,22] These defects could act as compensators of p-type dopant. For vertical power devices, the presence of such defects could show detrimental effects to the electric properties and the reliability of devices.…”
Section: Introductionmentioning
confidence: 99%
“…Using this technique, the implantation-induced strain is effectively removed, [12] and high acceptor activation percentages greater than 80% respective to implanted magnesium (Mg) ions have been obtained. [10,13,14] Unfortunately, prolonged annealing at high temperatures can promote the diffusion of Mg atoms so that the dopant dispersion profile is changed. [10,[13][14][15] Sakurai et al [15] reported that the diffusion coefficient for Mg atoms in GaN was 30 times larger than that for Mg in epitaxially grown Mg-doped GaN.…”
Section: Introductionmentioning
confidence: 99%
“…[10,13,14] Unfortunately, prolonged annealing at high temperatures can promote the diffusion of Mg atoms so that the dopant dispersion profile is changed. [10,[13][14][15] Sakurai et al [15] reported that the diffusion coefficient for Mg atoms in GaN was 30 times larger than that for Mg in epitaxially grown Mg-doped GaN. This finding suggests that dopant diffusion is enhanced by the formation of point defects during implantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation